THE INFLUENCE OF PRODUCT UNIQUENESS ON PURCHASING DECISIONS WITH BRAND AMBASSADOR AS A MODERATING VARIABLE - Ira Ningrum Resmawa; Camelia Rizki Agrina; Farida Akbarina; Suratman Suratman; Nurdin Nurdin; Abdul Razak Munir (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract This research is a quantitative study with an explanatory approach, namely an approach that relies on a number of previous studies as an initial foundation for building articles with the latest variations. The data used in the article is primary data that researchers obtained from 500 JNT employees spread throughout Indonesia. The data that was successfully collected was analyzed using the smart PLS 4.0 analysis tool. The result in this reserach show that the researcher's assumption regarding the Product Uniqueness variable can have a positive relationship direction and a significant influence on Purchasing Decisions can be accepted because the P-Vlues value is positive and below the significance level of 0.05, namely 0.014. In the second hypothesis, the researcher speculates with various credible research sources that the Brand Ambassador variable can strengthen the influence of the Product Uniqueness variable on Purchasing Decisions. The results of the second row of the third table of the Path Efficiency above show concomitant results because the P-Values also point to positive and are below the significance level of 0.05, namely 0.000, which is more significant than direct testing of 0.014. This indicates that the better the Brand Ambassador owned by a product, the more the product is known to the public until it can finally strengthen the occurrence of Purchasing Decisions. Thus, the first and second hypotheses in this study can be accepted and proven. Keywords: Product Uniqueness, Purchasing Decisions , Brand Ambassador